Personality Traits and Further Training - Laible, Marie-Christine; Anger, Silke; Baumann, Martina (Frontiers in Psychology, 2020)
The notion of lifelong learning is gaining importance, not only in the labor market but also in other areas of modern societies. Previous research finds variation in occupation-related training participation between different worker types, social groups, and personalities. However, evidence on the individual’s personality traits creating favorable conditions for further general or non-occupation-related training is scarce. To close this research gap, we analyze the role of personality for further training participation and compare how the Big Five Personality Dimensions relate to different training types by differentiating between non-formal and informal training measures. Furthermore, we investigate how personality traits affect further training chosen for occupational and private reasons. Using six waves of the Adult Stage of the German National Educational Panel Study (NEPS), we find that the relationship between personality traits and training participation varies according to the training type and the reason for participating in further training. Throughout our estimations, and for each training type, openness to experience is the most important determinant among the Big Five Personality Dimensions. This personality trait always positively relates to further training participation. Separate regressions for men and women reveal gender-specific differences in the importance of personality traits. Similarly, we show that different personality traits matter when the individual chooses the further training for private compared to work-related reasons. We conclude that socio-emotional skills are an important predictor of lifelong learning decisions.